Pengaruh Knowledge Management, Komunikasi dan Kepuasan Kerja Terhadap Kinerja Pegawai - Graciano Kevin Saputra; Kusuma Chandra Kirana; Mohammad Ahyar Syafwan Lysander (Indonesian Journal Publisher, 2025)
This study aims to analyze the simultaneous influence of knowledge management, organizational communication, and job satisfaction on employee performance at Yayasan Dian Yosefa Labuan Bajo. A quantitative approach was employed, involving hypothesis formulation, data collection from all 74 employees at the foundation's Labuan Bajo branch, and data analysis using linear regression. The independent variables examined were knowledge management, communication, and job satisfaction, while the dependent variable was employee performance. The results indicate that these three variables simultaneously have a positive and significant effect on employee performance. These findings highlight the importance of effective knowledge management, open communication, and job satisfaction in enhancing organizational productivity. In conclusion, the integrated management of these factors is critical for optimizing employee performance and achieving organizational goals, particularly in nonprofit educational institutions. The study recommends further research with a broader organizational context and the inclusion of qualitative methods to gain deeper insights.